The Cardboard Textbook: Inclusion and Access to Information from Collaborative Work - Viera, Iván Ariel (2022)
This essay aims to analyze the possibilities of a process of social inclusion by linking the way of working of a cardboard publisher and its strength as a social movement, with the aim of reflecting on the opportunities of generating inclusive actions to democratize access to information. This publisher finds its anchor in the publisher-society binomial and in the knowledge that is put into play as capital to satisfy the needs of the links that are generated. It will inquire how their policies make the problem of social exclusion and the marginalization of vulnerable sectors visible. The focus will be placed, then, on the activity of the cardboard publisher with respect to the form of cooperative and collaborative work and its possibilities as a form of social inclusion.